2023
DOI: 10.1126/science.add5190
|View full text |Cite
|
Sign up to set email alerts
|

Limited climatic space for alternative ecosystem states in Africa

Abstract: One of the foundational premises of ecology is that climate determines ecosystems. This has been challenged by alternative ecosystem state models, which illustrate that internal ecosystem dynamics acting on the initial ecosystem state can overwhelm the influence of climate, and by observations suggesting that climate cannot reliably discriminate forest and savanna ecosystem types. Using a novel phytoclimatic transform, which estimates the ability of climate to support different types of plants, we show that cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…In interpreting model output of forest probability, a probability range of 40%-60% was interpreted as indicative of a zone where forest presence was indeterminant, and it should be noted that this interpretation is somewhat arbitrary, and wider bounds would result in a conclusion of greater area of indeterminant vegetation. However, our zone of indeterminacy does concur with recent work identifying a limited zone of ASS in Africa based on climatic suitability for various plant growth forms (Higgins et al 2023). Furthermore, a wide cover range definition of bistability would undermine the concept by artificially emphasizing the continuous cover gradient between the distinct forest and savanna biomes.…”
Section: Bistability Of Tropical Forest and Savannasupporting
confidence: 76%
“…In interpreting model output of forest probability, a probability range of 40%-60% was interpreted as indicative of a zone where forest presence was indeterminant, and it should be noted that this interpretation is somewhat arbitrary, and wider bounds would result in a conclusion of greater area of indeterminant vegetation. However, our zone of indeterminacy does concur with recent work identifying a limited zone of ASS in Africa based on climatic suitability for various plant growth forms (Higgins et al 2023). Furthermore, a wide cover range definition of bistability would undermine the concept by artificially emphasizing the continuous cover gradient between the distinct forest and savanna biomes.…”
Section: Bistability Of Tropical Forest and Savannasupporting
confidence: 76%
“…While in principle any suitability or species distribution model could be used in the workflow, in practice, many existing alternative models may be inappropriate for this task. First, correlative suitability models have limited transferability 33 , 44 , producing implausible growth-form suitability surfaces 24 , whereas the process-based TTR-SDM used here was successful in model transferability tests 33 and produces plausible suitability surfaces 24 , 30 . Second, alternative models do not consider how elevated atmospheric CO 2 concentrations may influence photosynthesis and thereby species ranges.…”
Section: Resultsmentioning
confidence: 95%
“…The premise of this analysis is that we can characterize changes in the climatic forcing of ecosystems by analysing shifts in climatic suitability for the growth forms that define ecosystems. Previous work showed that the growth-form suitability values are useful predictors of ecosystem states 30 , suggesting that shifts in growth-form suitability may be useful indicators of the changing climatic forcing. It should be emphasized that the growth-form suitability may be quite different from growth-form abundances because other ecological processes such as biotic interactions, dispersal or disturbances, determine whether physiological suitability can predict abundance.…”
Section: Mainmentioning
confidence: 99%
“…Species distributions are also typically explained at the macroclimate scale only, despite the existence of alternative drivers (Schwilk & Keeley, 2012;Pausas & Bond, 2021). A recent example is the prediction of African vegetation using a plant growth model applied to species distribution and variables (Higgins et al, 2023). While the model may correctly predict some current vegetation, it fails to incorporate the most important ecological mechanisms that shaped African vegetation, such as large herbivores and frequent fires (Bond, 2019;Owen-Smith, 2021).…”
Section: Beyond Seed Ecologymentioning
confidence: 99%